If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(6p + -5) + 2p = 8p + -8 Reorder the terms: -2(-5 + 6p) + 2p = 8p + -8 (-5 * -2 + 6p * -2) + 2p = 8p + -8 (10 + -12p) + 2p = 8p + -8 Combine like terms: -12p + 2p = -10p 10 + -10p = 8p + -8 Reorder the terms: 10 + -10p = -8 + 8p Solving 10 + -10p = -8 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 10 + -10p + -8p = -8 + 8p + -8p Combine like terms: -10p + -8p = -18p 10 + -18p = -8 + 8p + -8p Combine like terms: 8p + -8p = 0 10 + -18p = -8 + 0 10 + -18p = -8 Add '-10' to each side of the equation. 10 + -10 + -18p = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -18p = -8 + -10 -18p = -8 + -10 Combine like terms: -8 + -10 = -18 -18p = -18 Divide each side by '-18'. p = 1 Simplifying p = 1
| 2(0,3x-1)-0,6=4+0,1x | | 8+10y=9y-6 | | -16t^2+57=0 | | 17x=6x-22 | | 138-4x=32x+22 | | 10.5=3b-12.5 | | 4x+2x+96-22=88+4x | | 6-3x-5x-1=10 | | 4(3x-44)=4(2x-10) | | 4x^4-17x^2+18=0 | | 5x*3+17=69+2x | | -2(3x-4)+12=8 | | -16t^2+7.85t+57=0 | | 4-x-2-x=x | | 5x^2+4xy-12y^2=0 | | 4-x-2+x=x | | 189.028=2*3.14*r^2+2*3.14*r*2.7 | | 6a+8b=1500 | | 3t-6=2t+2 | | -3x+8=-1 | | (3x*7)=21 | | 4x+2+7x-19=180 | | 10x^2+8x^4= | | -16t+7.85t+107=0 | | -18=-6-3x | | 4=2(5-x) | | 5y-7-6y=-9 | | 3(3-x)+2x=8-2(x-1) | | 3/4+8=5 | | 3x-4x-x=x-6 | | 9(x-5)=18 | | 2(3x-7)=2(x+5) |